Lean-Kaizen operations model for improving intralogistics in a construction materials SME: a study from Peru - Sanchez Roman, Gabriela Yamile (2025)
The operational performance of construction material and hardware retail SMEs in Peru has long been constrained by inefficient logistics systems and inadequate process standardization. Previous research has offered theoretical models with limited empirical validation, especially in resource-constrained environments. This study addressed critical inefficiencies such as disorganized warehouses, extended picking and loading times, and high defect rates. It proposed a Lean-Kaizen operations model built on 5S, visual management, and standardized work practices. The implementation over four months resulted in measurable improvements, including a 26% increase in OTIF and a 63% reduction in defective materials. Search and loading times decreased by 33% and 36%, respectively, reflecting enhanced productivity and worker satisfaction. These results underline the model’s potential for transformative impact on operational efficiency. Academically, the study contributes practical evidence to the field of industrial engineering. Socioeconomically, it strengthens SME competitiveness. Further exploration is encouraged to adapt this framework across sectors and regions facing similar logistical challenges.